Disruption of mitochondrial fitness in human preadipocytes by fatty acids - Rogers, Artie Carlyle (East Carolina University, 2013)
Adipose tissue lies at the core of energy metabolism, by not only releasing and taking up fatty acids (FA) according to the individuals overall surplus or deficit of energy, but also signaling other tissues to regulate their own metabolism. In the event that adipose tissue function is lost, insulin resistance, hypertriglyceridemia and hepatic steatosis can develop. Despite the wealth of knowledge that exists for how mature adipocytes function in both normal and diseased states, preadipocytes, which can safe guard against adipocyte dysfunction by differentiating and joining the adipocyte pool, have been overlooked. Therefore, how human preadipocytes function in the presence of a mixture of FA (oleate, palmitate, stearate and linoleate) that resembles a healthy individual's adipose tissue microenvironment was investigated. Experiments using a novel real-time flow cytometry device show that the maximal rate of mitochondrial superoxide accumulation, hydrogen peroxide (H2O2) production, and lipid peroxidation occurred within seconds of exposure to FA. Although mitochondrial ROS occurred in a transient fashion (within 2 hours), preadipocytes still experienced a loss in respiration through depletion of NAD+ and NADH that manifested into overt oxidative stress and cell death after 24 hours of FA exposure. Despite observing cell death in 35% of our population, the majority of preadipocytes were able to mount a protective response through increases in the mitochondrial antioxidant buffering capacity. Investigation into FOXO1, one of the transcription factors that govern mitochondrial antioxidant gene transcription, revealed an increase in deacetylation as soon as six hours post FA exposure. Inhibition of FOXO1 or SIRT1, which deacetylates FOXO1, exacerbated the toxic effects of FA suggesting that the SIRT1-FOXO1 axis may play a beneficial role in protecting preadipocytes from constant exposure to FA. Furthermore, SIRT1, FOXO1 and mitochondrial antioxidant gene expression from human adipose tissue was correlated to insulin sensitivity further highlighting the potential importance of mitochondrial antioxidant buffering systems in adipose tissue function. Altogether, this study suggests that the preadipocyte survivability is centered on mitochondrial resistance to FA-induced ROS through up regulation of mitochondrial antioxidant systems.
Keywords: Pharmacology; Adipose tissues; Fatty acids; FOXO1; Mitochondria; Preadipocytes; SIRT1; Adipose Tissue--growth & development; Adipocytes; Forkhead Transcription Factors; Humans; Insulin Resistance; Hypertriglyceridemia; Fatty Liver; Sirtuin 1